Median survival following geriatric hip fracture among 17,868 males from the Veterans Health Administration - Lee, Alexander; Xi, Ianto Lin; Ahn, Jaimo; Bernstein, Joseph (Frontiers in Surgery, 2023)
Background The expected value of treatments for geriatric femoral neck fracture is influenced by the predicted duration of survival after injury. Specifically, total hip arthroplasty is more suited for patients likely to live long enough to reap its longer-term benefits. For predicting short- and medium-term survival, there are many tools available, but for longer-term survival prognosis the current literature is insufficient. Our hypothesis is that patient age at the time of injury correlates with median life expectancy and survival rates, and these values can anchor a prediction regarding a given patient’s life expectancy. We therefore sought to determine median and fractional survival rates at 30 days, and 1, 2, 5 and 10 years after surgery for a large cohort of elderly patients with hip fracture as a function of age. Methods 17,868 male patients age 65-89 treated surgically for hip fracture within the Veterans Affairs system were assessed. From this set, 10,000 patients were randomly selected, and their ages at surgery and death (if any) were recorded at least 10 years post-operatively. Median and fractional survival rates were recorded at 1 month and 1, 2, 5, and 10 years. The mathematical relationship between age and median survival was determined. All findings from the 10,000-patient cohort were compared to corresponding values of the remaining 7,868 patients, to assess the predictive power of the initial observations. Results The median survival rate for the entire cohort was 2.2 years, with 90.4% of the group surviving at day 30 days. The percentage of the cohort surviving at 1, 2, 5 and 10 years after treatment was 64.5%, 52.3%, 27.1% and 8.9% respectively. Median survival was approximately (3 – (0.13 x age-at-time-of-surgery) years for patients of all ages. Conclusions Median survival after geriatric hip fracture can be accurately predicted by the patient’s age at the time of injury. Median survival and fractional survival at key milestones can help estimate life-expectancy and thereby help guide treatment.